Sikap Republika.co.id terkait Kasus Dugaan Penistaan Agama oleh Sukmawati Soekarnoputri (Jurnal Kajian Media, 2020)
Abstract - The alleged blasphemy case by Sukmawati Soekarnoputri surely has been widely reported by the mass media, both print media, electronic media, and online media. In this case, each media has a different way to package of frame a story. Those framing was formed by a media depending on the interest of the media itself, so that the news has displayed cannot be separted from its alignments. Then this research should be conducted to find out how Republika.co.id attitude is related to the alleged blasphemy case by Sukmawati Soekarnoputri. The object of research is news regarding the alleged blashphamy case by Sukmawati Soekarnoputri in the period 17-19 November 2019. This research uses a constructivist paradigm with a qualitative approach. The research method used in this study is framing analysis by Robert M. Entman which has two large dimensions, namely issue selction and highlighting aspects as well as four elements namely define problems, diagnose causes, make moral judgement, and treatment recommendation. The result of the study showed that Republika.co.id showing it’s attitude of alingnments. Republika.co.id claimed that Sukmawati Soekarnoputri had violated criminal code on religious defamation, therefore this case should be processed legally not only resolved by apologize to the muslim community as well as she did when she composed a poem which is considered to alleged blasphemy. Keywords: News; Framing; Online Media; Defamation of Religion; Sukmawati Soekarnoputri